Indias Water Dispute with Neighbouring Countries with Special Reference to Pakistan Bangladesh and Nepal: Exploring the geopolitical dynamics of water disputes in South Asia (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Water has an incredible importance on our planet. It covers multiple thirds of the world's surface and includes multiple thirds of sythesis of individual. Life on earth began with water and without water life can't proceed. Water is a fundamental asset to all parts of a nation's endurance, from its occupant science to their economy. Underlining the significance of water prominent Greek Philosopher, Pinder, said that the best of all things is water. For most people past chronicled figuring water is a blessing from God. In Africa water is related with moves, while in India the appearance of rainstorm is praised in specific areas. Water vows to be the 21st century what oil was to twentieth century the valuable item that decides the abundance of countries. 1 There are numerous cases of immediate and roundabout contentions over water. However, from the most recent century water turned into a quarrelsome issue and a wellspring of intense struggles among various nations. As human populace develops, way of life changes, and with it, the interest for new water and climatic inconstancy make water organic market dangerous and unsure.